2020
DOI: 10.1101/2020.08.31.20185157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of Hyperglycemia With Hospital Mortality in Covid-19 Patients Without Diabetes: A Cohort Study

Abstract: Objective: Diabetes is a known risk factor for mortality in Coronavirus disease 2019 (COVID-19) patients. Our objective was to identify prevalence of hyperglycemia in COVID-19 patients with and without diabetes and quantify its association with COVID-19 disease course. Research Design and Methods: In this observational cohort study, all consecutive COVID-19 patients admitted to John H Stroger Jr. Hospital, Chicago, IL from March 15, 2020 to May 15, 2020 were included. The primary outcome was hospital mortalit… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Hyperglycemia on hospital admission in severely ill people with COVID-19 is very well recognized and is predictive of a poor outcome, even in subjects without pre-existing diabetes ( Cai et al., 2020 ; Fadini et al., 2020 ; Huang et al., 2020b ; Mamtani et al., 2020a ). For example, dysregulated glucose control was associated with poor outcomes in 1,122 hospitalized people with COVID-19 analyzed in the Glytec database from March 1 to April 6, 2020 ( Bode et al., 2020 ).…”
Section: Glucose Control and Covid-19 Outcomesmentioning
confidence: 99%
“…Hyperglycemia on hospital admission in severely ill people with COVID-19 is very well recognized and is predictive of a poor outcome, even in subjects without pre-existing diabetes ( Cai et al., 2020 ; Fadini et al., 2020 ; Huang et al., 2020b ; Mamtani et al., 2020a ). For example, dysregulated glucose control was associated with poor outcomes in 1,122 hospitalized people with COVID-19 analyzed in the Glytec database from March 1 to April 6, 2020 ( Bode et al., 2020 ).…”
Section: Glucose Control and Covid-19 Outcomesmentioning
confidence: 99%
“…IL-6) will induce or worsen insulin resistance and disrupt the insulin secretion. Zhou et al 6 and Mamtani et al 5 in their studies showed that elevation of proinflammatory cytokines in circulation, such as CRP, IL-6, Interferon Gamma, and Tumor Necrosis Factor Alpha occured in hyperglycemic patients either with diabetes or without diabetes. Sachdeva et al 8 found that IL-6 level decreased after the hyperglycemia was treated.…”
Section: Hyperglycemia In Covid-19mentioning
confidence: 99%
“…Secondly, an indirect mechanism was found via the impact of pro-inflammatory cytokines, acute stress factors, or a history of glucocorticoid therapy usage. 5 SARS-CoV-2 could damage pancreatic β cells by binding to ACE-2 receptor, hence insulin secretion is impaired. As a consequence, blood sugar level will increase and worsen the diabetes condition or induce hyperglycemia in patients without prior diabetes.…”
Section: Hyperglycemia In Covid-19mentioning
confidence: 99%
See 2 more Smart Citations